2013
DOI: 10.3109/07853890.2013.810891
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ‘activity monitor-based’ counseling on physical activity and health-related outcomes in patients with chronic diseases: A systematic review and meta-analysis

Abstract: Activity monitor-based counseling had a beneficial effect on PA, HbA1c, systolic blood pressure, and BMI in patients with DMII. Data in patients with COPD and CHF are limited or non-existing, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 69 publications
5
85
2
5
Order By: Relevance
“…Since it is important that subjects with COPD integrate physical activity in their daily life, education and counselling should be an important component of programmes targeting physical activity. Indeed, it has previously been shown that activity monitor-based counselling has a beneficial effect on physical activity and health-related outcomes in patients with chronic diseases [28]. Stimulating physical activity and prevention of a sedentary lifestyle in the earliest stages of COPD may not only result in less adverse health-related consequences and a reduction in healthcare utilisation and costs [8], but also in better survival.…”
Section: Discussionmentioning
confidence: 99%
“…Since it is important that subjects with COPD integrate physical activity in their daily life, education and counselling should be an important component of programmes targeting physical activity. Indeed, it has previously been shown that activity monitor-based counselling has a beneficial effect on physical activity and health-related outcomes in patients with chronic diseases [28]. Stimulating physical activity and prevention of a sedentary lifestyle in the earliest stages of COPD may not only result in less adverse health-related consequences and a reduction in healthcare utilisation and costs [8], but also in better survival.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that objective feedback from one's own performance can contribute favorably to learning of motor skills [23] and maintain motivation to continue the training program [34]. However, conventional physical activity monitoring devices, such as pedometers and motion sensors, are incapable of assessing exerciser's performance such as RT, intensity, and rhythmic synchrony of body movements with respect to instructor's demonstration movements.…”
Section: Discussionmentioning
confidence: 99%
“…Проблема состоит в постоянном поддержании необходимого уровня физической на грузки, при этом выявлены поведенческие факторы, связанные с повседневной ФА и разработкой новых методов лечения. У больных ХОБЛ можно добиться изменения образа жизни и повышения повседневной ФА с помощью самомониторирования ФА с использо ванием мониторов в сочетании с поведенческими консультациями [45][46][47][165][166][167]. Однако доказа тельная база, подтверждающая эффективность тако го подхода, весьма немногочисленна: проведено все го несколько исследований при небольшой выборке пациентов [46,47], нередко без контрольной груп пы [45,165,166].…”
Section: изменение образа жизни обратная связь консультацииunclassified